Association between maternal sugar-sweetened beverage consumption and the social-emotional development of child before 1 year old: A prospective cohort study - Gao, Rui; Liu, Xuemei; Li, Xiuxiu; Zhang, Yuanxing; Wei, Min; Sun, Peng; Zhang, Jianan; Cai, Li (Frontiers in Nutrition, 2022)
Background Excessive consumption of sugar-sweetened beverages (SSBs) has become an international public health issue. Adverse effects of sugary beverage consumption on both mother and child during pregnancy continue to be found. However, evidence regarding maternal SSB consumption and social-emotional development of children is lacking. Methods Based on the Shenzhen Birth Cohort Study (loss rate: 10.97%), we included 985 mother-infant pairs from 2018 to 2022. All mothers had a singleton live birth without hypertension, diabetes, tumor, or serious immune system disease before pregnancy. We used a chart of frequency distribution to show maternal SSB consumption, including non-diet soda, tea drinks (not 100% tea), fruit drinks, Sugar-sweetened coffee, bubble tea, or cocoa drinks, and total SSBs. A multivariate logistic regression model was used to estimate the odds ratios of the potential delay on social-emotional development of each child was monitored at both 6 months and 12 months of age based on maternal SSB consumption. Results Among the mothers, 728 (73.91%) drank SSBs <1 time per week, 194 (19.70%) drank SSBs 1–2 times per week, 43 (4.37%) drank SSBs 3–4 times per week, and 20 (2.03%) drank SSBs 5 or more times per week. Children aged 12 months with mothers who drank SSBs five or more times per week during pregnancy had an increased risk of potential delay on social-emotional development compared to those with mothers who drank SSBs less than once per week [odds ratio: 3.08 (1.13–8.39)]. Regarding the specific kinds of SSBs, we found that tea drinks (not 100% tea) were positively associated with potential delay on social-emotional development in children aged 6 months. Conclusion Nearly three-quarters of mothers consumed almost no SSBs during pregnancy. High SSB intake during pregnancy was associated with an increased risk of the potential delay on social-emotional development of a child at 6 and 12 months of age.